2007
DOI: 10.1089/scd.2007.0014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of NF-κB Expression and Activity Upon Differentiation of Human Embryonic Stem Cell Line SNUhES3

Abstract: NF-kappaB is involved in many biological processes including proliferation, survival, and differentiation. Because human embryonic stem (ES) cells have the potential to differentiate to various lineages, understanding mechanisms involved in stemness and lineage differentiation is an important issue. We investigated expression of NF-kappaB in the human ES cell lines SNUhES3 and MizhES4 and found that expression of NF-kappaB mRNA and protein in these two cell lines was significantly lower compared to those of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
35
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 35 publications
16
35
1
2
Order By: Relevance
“…We have shown that activation of NFkB is upregulated during differentiation of GICs. In agreement with this, it has been described that expression and activity of NFkB is comparatively low in undifferentiated embryonic-initiating cells, but increases following induction of differentiation (Kang et al, 2007;Torres and Watt, 2008). The low activation of NFkB detected in GICs suggests that NFkB may be dispensable for survival and proliferation of these tumor NFjB blockade promotes senescence of differentiating GICs L Nogueira et al progenitor cells, which correlates with data showing that p65 immunoreactivity is abundant in the cytoplasm of the majority of cells within neurospheres derived from embryonic mouse brain, but only occasional weak nuclear localization (active state) is detected (Young et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…We have shown that activation of NFkB is upregulated during differentiation of GICs. In agreement with this, it has been described that expression and activity of NFkB is comparatively low in undifferentiated embryonic-initiating cells, but increases following induction of differentiation (Kang et al, 2007;Torres and Watt, 2008). The low activation of NFkB detected in GICs suggests that NFkB may be dispensable for survival and proliferation of these tumor NFjB blockade promotes senescence of differentiating GICs L Nogueira et al progenitor cells, which correlates with data showing that p65 immunoreactivity is abundant in the cytoplasm of the majority of cells within neurospheres derived from embryonic mouse brain, but only occasional weak nuclear localization (active state) is detected (Young et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…Previously, we reported that expression and activity of NF-κB is comparatively low in undifferentiated human ES cells, but its expression increases during differentiation of ES cells when induced by retinoic acid (23). Recently, we also confirmed this phenomenon in mouse ES cells (24), which suggest that low NF-κB expression and activity is relevant in different species, and that NF-κB may contribute to differentiation rather than self-renewal of ES cells.…”
Section: Introductionsupporting
confidence: 55%
“…Recently, we also confirmed this phenomenon in mouse ES cells (24), which suggest that low NF-κB expression and activity is relevant in different species, and that NF-κB may contribute to differentiation rather than self-renewal of ES cells. Accordingly, TNF-α (23,24) and many other NF-κB agonists do not activate the NF-κB pathway in either human or mouse ES cells (our unpublished data). A recent report by other investigators also suggested a differentiation inducing activity of NF-κB in mouse ES cells (25).…”
Section: Introductionmentioning
confidence: 73%
“…Deste modo, de acordo com os membros da família que estão envolvidos na ativação da via, dá-se a Interessantemente, estudos realizados anteriormente em nosso grupo mostraram por análise de expressão gênica que células-tronco hematopoéticas primitivas de cordão umbilical quando comparadas com células da melula óssea apresentaram alta expressão de fatores de transcrição relacionados com a hematopoiese primitiva e a auto-renovação, entre eles componentes chaves da via NFκB não canônica, RelB e NFΚB2, sugerindo que a via NFκB pode estar envolvida na regulação da pluripotência em células-tronco (PANEPUCCI et al, 2007). Outros estudos, muitos deles contraditórios, têm mostrado a participação dos componentes da via canônica e não-canônica de NFκB nos processos de diferenciação e destino celular ou manutenção da pluripotência (ARMSTRONG et al, 2006;KANG et al, 2007; LÜNINGSCHRÖR; KALTSCHMIDT;KALTSCHMIDT, 2012;YANG et al, 2010).…”
Section: Vias De Sinalização Nfκbunclassified
“…Quando as linhagens de células-tronco embrionárias foram induzidas à diferenciação com atRA durante 6 dias passaram a expressar RelA e NFΚB1 e houve uma diminuição da expressão de OCT4 e NANOG, assim como visto em nossos resultados realizados com NTera-2 em 4 dias de tratamento com atRA. O grupo relatou ainda que a ativação extrínseca de RelA por TNF-α em células indiferenciadas e em células diferenciadas por atRA, resultava em migração desta subunidade para o interior do núcleo, foi detectável apenas nas células diferenciadas, evidenciando por imunofluorescência que a atividade de RelA era muito baixa em células-tronco embrionárias e que a sua expressão, bem como ativação, era um processo que surgiria no processo de diferenciação celular (KANG et al, 2007).…”
Section: Rt-qpcr Dos Genes Das Vias Canônica E Não Canônica De Nfκbunclassified